Experiência no Treinamento de Servidores Públicos Municipais em Software de Geoprocessamento Gratuito no Brasil - Schuch, Fernanda Simoni; Loch, Carlos (Revista Brasileira de Cartografia, 2011)
In the years of 2008 and 2009 it was realized a training program to municipal civil servants of thirty eights city halls in the state of Santa Catarina in Brazil. It happened through the PROEXT 2007 program developed by the Cities and Education Ministry with the objective of providing the servants courses of the following subjects: remote sensing, cartography, global positioning system and information systems. This paper has as goal to describe the training applied trough short-time courses, the profile of the students, professionals from Santa Catarina’s city halls, users of the cartography products produces in Brazil. It is presented in this paper a brief description of the software used at the course: GeoSNIC, TerraView and TerraSIG, developed by Brazilian institutions and freely made available on the internet. For leveling the technical knowledge of the participants theoretical classes were given with practical ones in sequence to practice the software. The heterogeneity of the previous academic knowledge of the students made the course to be planned and executed seeking for a leveling of the technical content challenging the executor tem of the project. In the end, the software proved to be an important tool to municipal public management, efficient in their functionalities if compared to proprietary software.